Method for testing interfacial shear strength of SiCf / SiC ceramic matrix composite fiber matrix
By collecting acoustic emission signals and stress-strain curves during the continuous tensile loading of standard splines of SiCf/SiC composites, combined with fracture observation, the accuracy of interface shear strength measurement and high-temperature testing problems in the prior art are solved. Accurate measurement of the interface shear strength and fracture energy of SiCf/SiC composite laminates is achieved, simplifying the testing process and reducing costs.
Patent Information
- Application Number
- CN202411583097.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art has many defects in measuring the interface shear strength of SiCf/SiC composite fiber matrix, including fracture fiber extraction length statistics, crack statistics and single fiber ejection method, which has low data accuracy and subjectiveness. Strong performance, difficult sample preparation and inability to test at high temperature.
The acoustic emission signal, stress-strain curve, and sample fracture observation during the continuous tensile loading of standard splines were used to calculate the interface shear strength of the fiber matrix and The fracture energy of the matrix simplifies the test process and is suitable for room temperature and high temperature testing.
It improves the accuracy of interface shear strength measurement and high-temperature testing capabilities, simplifies the testing process, reduces costs, overcomes the subjectivity of existing methods and sample preparation problems, and can truly reflect the performance of SiCf/SiC composite laminates.
Smart Images

Figure CN119246277A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite material mechanical property testing, and specifically relates to a method for testing SiC f Method for determining the shear strength of fiber-matrix interface of SiC ceramic matrix composites. Background Art
[0002] Effect of fiber matrix interface shear strength on SiC f The interface shear strength has an important influence on the final macroscopic mechanical properties of SiC composites. Too high interface shear strength causes brittle fracture of the composites, while too low interface shear strength leads to ineffective load transfer. Interface shear strength is a bridge between the interface phase characteristics and macroscopic mechanical properties of composites, and is also a weather vane guiding the preparation and process optimization of the interface phase of composites.
[0003] Currently SiC f The main measurement methods for the fiber-matrix interface shear strength of SiC / SiC composites include four methods: fiber pull-out length statistics at fracture, crack statistics, single fiber push-out and single fiber push-in.
[0004] There are two disadvantages of the fracture fiber pull-out length statistical method: ① It is difficult to test the Weibull parameter of the fiber in-situ strength; ② The statistical workload of the fracture fiber pull-out length is large, the subjectivity is strong, and the data accuracy is not high. The crack statistical method is generally applicable to mini-composites, including two methods: crack number statistics and saturated crack spacing statistics.
[0005] The crack number counting method is to perform cyclic loading on the bundled wire composite material, and use the width of the last loading-unloading loop before the bundle failure (δΔ) and the number of matrix cracks (N) within the test span after failure to calculate the fiber-matrix interface shear strength. The crack number counting method is relatively complicated, requiring cyclic loading, and each loading-unloading process has a certain degree of randomness. In addition, this method is highly subjective, has a large workload, and is prone to omissions.
[0006] Similar to the crack number statistics method, the crack spacing statistics method also calculates the interface bonding strength by counting the cracks after the failure of the bundled filament composite material, but the process is relatively simple, and direct loading can be performed without the need for cyclic loading. The fiber-matrix interface shear strength is calculated by counting the matrix crack saturation crack spacing. The defect of this method is that it is necessary to identify the load corresponding to crack saturation on the load-displacement curve. In the specific implementation process, there are large subjective factors in the interpretation of the crack saturation area, and it is difficult for many samples to present a load-displacement curve that can accurately identify the load when the crack is saturated. In addition, similar to the crack number statistics method, the crack spacing statistics method also has the problems of strong subjectivity and inaccuracy.
[0007] The single fiber ejection method requires the preparation of a composite sheet with a thickness of less than 100 μm, and then the single fiber is loaded by nanoindentation (flat indenter), the load-displacement curve is recorded, and then the fiber-matrix interface shear strength of the composite material is calculated according to the theoretical formula. This method also has two shortcomings: ① SiC f 1. The high hardness and brittleness of SiC / SiC composites make it difficult to prepare thin slice samples containing several complete fibers; 2. The thin slices are easy to destroy the mechanical environment of the composite material during the grinding preparation process, causing changes in the interface bonding strength or even interface debonding, affecting the test results. The above factors make the single fiber ejection method less and less used.
[0008] The single fiber push-in method requires cutting a small sample from the material so that the fiber cross section is parallel to the sample surface, and finally embedding it in resin for polishing. Then, with the help of a precise nanoindentation micromechanical testing device, the single fiber is loaded and the fiber-matrix interface shear strength is calculated based on the critical load on the load-displacement curve. Compared with the ejection method, the single fiber push-in method has obvious advantages in test efficiency. However, this method is significantly different from the working condition of the fiber being pulled out of the matrix during the tensile loading process of the real material. The deformation of the fiber during the fiber push-in process will also introduce significant errors. In addition, this method still cannot solve the problem of fiber-matrix interface shear strength testing at high temperatures. Summary of the invention
[0009] The purpose of the present invention is to overcome the disadvantages of existing interface strength micromechanics test methods that require separate sample preparation and the technical problems of fiber matrix interface shear strength test at high temperature. f The method for determining the shear strength of the fiber-matrix interface of SiC ceramic matrix composites is based on the acoustic emission signal, stress-strain curve, and fracture observation of the sample after the sample is broken during continuous tensile loading of the standard spline. f / SiC composite laminate material fiber matrix interface shear strength and matrix fracture energy.
[0010] To solve this technical problem, the technical solution of the present invention is:
[0011] A test SiC f A method for determining the shear strength of a fiber-matrix interface of a SiC ceramic matrix composite material, the steps being as follows:
[0012] Step 1: On SiC f / SiC composite material pure 0° laminated cutting tensile test pieces;
[0013] Step 2: Clamp the tensile test piece onto the test machine clamp, install the extensometer onto the middle working section of the test piece, and install the acoustic emission probe onto the surface of the gauge section of the test piece or onto the acoustic emission signal lead-out device.
[0014] Step 3: Use displacement loading mode to perform tensile loading on the test piece, collect acoustic emission signals during the loading process, and record the stress-strain curve measured by the extensometer and the testing machine, and continue loading and collecting data until the test piece breaks;
[0015] Step 4: Remove the broken test piece, and cut a rectangular strip of the same thickness as the test piece from the middle of the width direction near the fracture of the working section of the test piece after the fracture, as a mirror sample;
[0016] Step 5: polishing one side of the mirror image sample in the width direction with diamond paste;
[0017] Step 6: Observe the polished side of the mirror sample using a scanning electron microscope, perform margin segmentation on the image using the image processing software provided by the electron microscope, identify matrix cracks according to the difference in grayscale values, and mark them on the image;
[0018] Step 7: Using the image (the image with matrix cracks marked above), count the matrix crack spacing and calculate the average value to obtain the matrix crack spacing Z of the sample in a completely fractured state. u ;
[0019] Step 8: Using the time, load, strain, and acoustic emission energy data collected during the tensile test loading process, with time as the link, the stress and the normalized acoustic emission cumulative energy values are matched to draw a curve with the stress as the abscissa and the normalized acoustic emission cumulative energy as the ordinate;
[0020] Step 9: According to the tensile stress-strain curve of the test piece, identify the stress value σ when the matrix crack is saturated s .
[0021] Step 10: The stress is σ obtained by subtracting the stress-normalized acoustic emission cumulative energy curve. s The normalized acoustic emission cumulative energy E corresponding to s .
[0022] Step 11: According to the law that the normalized acoustic emission cumulative energy is linearly proportional to the matrix density and thus linearly inversely proportional to the matrix crack spacing, the matrix crack spacing Z when the matrix crack is saturated is calculated according to formula (1): s ;
[0023]
[0024] Among them, Z sis the matrix crack spacing when the matrix crack is saturated; Z u is the matrix crack spacing when the specimen is completely fractured; E s is the normalized acoustic emission cumulative energy corresponding to the saturation of matrix cracks;
[0025] Step 12: Based on the stress value σ when the matrix crack is saturated, s , matrix crack spacing Z s , the fiber-matrix interface shear strength S is calculated using the theoretical formula (2), and the matrix fracture energy Γ is calculated using the formula (3) m .
[0026]
[0027] Where S is the fiber-matrix interface shear strength; R is the fiber radius; E m is the matrix modulus; E f is the fiber modulus; V f is the fiber volume fraction; σ s is the stress value when the matrix crack is saturated; Z s is the crack spacing when the matrix cracks are saturated.
[0028]
[0029] Among them, Γ m is the matrix fracture energy; E0 is the tensile modulus of the material, taken as the slope of the linear segment of the tensile stress-strain curve.
[0030] The method is applicable to a ceramic matrix composite material of a continuous SiC fiber reinforced SiC matrix by a layering process, and is particularly applicable to SiC prepared by a prepreg-melt infiltration process. f / SiC composite laminates.
[0031] The dimensions of the tensile test piece described in step 1 are based on GJB 6475-2008.
[0032] Preferably, in order to ensure the accuracy of the test, the length of the rectangular strip in step 4 is 3-5 times the thickness of the sample, and the width is 1-2 times the thickness of the sample, such as 5 mm in length and 3 mm in width.
[0033] Due to SiC f The crack density of the 0° ply in the laminate of 0v / 90° alternating ply of SiC composite material is linearly proportional to the normalized energy of the acoustic emission signal. f Pure 0° laminates of SiC composite materials can also be replaced with 0° / 90° alternating laminates.
[0034] The method of the present invention is applicable to testing at room temperature and high temperature, wherein the high temperature is 600-1400 degrees Celsius. When testing at room temperature, the acoustic emission probe is fixed and attached to the surface of the gauge section of the test piece with a clip. When testing at high temperature, a waveguide is used, one end of the waveguide is in contact with the sample, and the other end extends out of the high-temperature furnace, and the acoustic emission probe is fixed and attached to the end of the waveguide with a clip, and the acoustic wave signal during the loading process of the test piece is led out to ensure that the acoustic wave signal can be received by the acoustic emission probe. As a precision detection instrument, the acoustic emission probe can only be used below 150°C, and a waveguide must be used at high temperatures.
[0035] Steps 6 and 7 may also be performed by identifying matrix cracks and measuring the matrix crack spacing Z. u .
[0036] In step 9, the stress value σ at which the matrix crack is saturated is identified based on the tensile stress-strain curve. s The method is to mark the starting point of the last linear segment σ on the curve. s The corresponding stress value, as σ s .
[0037] Step 11 SiC f The normalized acoustic emission accumulated energy in pure 0° laminates of SiC / SiC composites is linearly proportional to the matrix density.
[0038] In step 12, the fiber-matrix interface shear strength S and matrix fracture energy Γ are calculated. m The fiber modulus E involved in the theoretical formula f , matrix modulus E m It is obtained by using nanoindentation testing technology. In other implementations, it can also be obtained by traditional macroscopic mechanical testing methods.
[0039] The beneficial effects of the present invention are:
[0040] The present invention is based on the one-to-one correspondence between the normalized energy, stress, and matrix crack spacing of the acoustic emission signal, determines the crack spacing under the saturated stress of the matrix crack, and introduces the theoretical formula based on the shear lag theory to calculate the test method of the fiber-matrix interface shear strength and the matrix fracture energy. The method of the invention can be based on the continuous loading of the standard tensile test piece, without the need to perform multiple cycles of loading-unloading-crack observation-reloading on the test piece, which can simplify the test process, avoid the stress-strain curve test deviation caused by non-continuous loading, and avoid the problem of low crack spacing measurement accuracy due to crack closure after unloading. In addition, this method can also be used for high temperature testing, which can effectively solve the problem of SiC under high temperature conditions. f / SiC composite fiber matrix interface shear strength and matrix fracture energy test. Compared with the existing technology, the advantages are:
[0041] (1) First, it solves the problem that existing methods cannot test SiC f / SiC composites at high temperatures and the problem of interface shear strength and matrix fracture energy.
[0042] (2) Based on the rule that the cumulative energy is linearly proportional to the crack density, the crack spacing under the matrix crack saturation stress is indirectly calculated by normalizing the acoustic emission cumulative energy, thereby measuring the interface shear strength and matrix fracture strength. Moreover, the interface shear strength measured by this method reflects the final prepared SiC f The properties of the SiC / SiC composite laminates, rather than the properties of the mini-composites separated from the bulk material, can more realistically characterize the fiber-matrix interface shear strength and matrix fracture strength of the final material.
[0043] (3) To overcome the disadvantage of existing interface strength micromechanical test methods that require separate sample preparation, it is only necessary to use conventional standard spline tensile tests to add acoustic emission signal collection and analysis and post-test fracture analysis to simplify the test. There is no need to specially prepare samples for micromechanical tests, and to use precise micromechanical test equipment. Only the data information obtained before and after the macro test can be used to measure the fiber-matrix interface shear strength and matrix fracture energy, greatly reducing the test cost.
[0044] (4) The existing microscopic testing methods based on matrix crack saturation stress all use load-displacement curves to identify the stress value when the matrix crack is saturated, which makes it difficult to ensure the accurate identification of this key stress parameter. The present method uses the stress-strain curve of the standard spline to identify the stress value when the matrix crack is saturated, which can greatly improve the identification accuracy of the stress value when the matrix crack is saturated.
[0045] (5) SiC of the present invention f The test method for fiber-matrix interface shear strength of SiC / SiC composite materials is suitable for testing the fiber-matrix interface shear strength and matrix fracture energy of ceramic-based composite materials with continuous SiC fibers reinforced SiC matrix in the lamination process. The operation process is simple and easy to realize engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the technical solutions implemented in the present invention, the following is a brief explanation of the drawings required to be used in the examples of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0047] Figure 1 It is a flow chart of the implementation of the present invention;
[0048] Figure 2 SiC fConfiguration and geometric dimensions of the standard tensile specimen of pure 0° ply of / SiC composite materials (unit: mm);
[0049] Figure 3 It is a schematic diagram of the test piece clamping and signal acquisition device installation;
[0050] Figure 4 It is a schematic diagram of taking a mirror image sample from the test piece after fracture;
[0051] Figure 5 The tensile stress-strain curve is obtained by measuring the pure 0° ply standard tensile spline.
[0052] Figure 6 Schematic diagram of the mirror sample and its sectioning.
[0053] Figure 7 Schematic diagram of the matrix crack and its crack marking in the mirror sample observed under an electron microscope.
[0054] Figure 8 The horizontal axis is stress, and the vertical axis is the curve of normalized acoustic emission cumulative energy.
[0055] in:
[0056] 1. Tensile test piece; 2. Upper wedge-shaped clamp of the testing machine; 3. Lower wedge-shaped clamp of the testing machine; 4. Acoustic emission probe for normal temperature test; 5. Extensometer; 6. Acoustic emission signal extraction device; 7. Acoustic emission probe for high temperature test; 8. High temperature furnace; 9. The left half of the test piece after fracture; 10. The right half of the test piece after fracture; 11. The left fracture of the test piece after fracture; 12. The right fracture of the test piece after fracture; 13. Obtain a mirror image sample near the left fracture; 14. Obtain a mirror image sample near the right fracture; 15. The polished side of the mirror image sample. DETAILED DESCRIPTION
[0057] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0058] The features of various aspects of the embodiments of the present invention will be described in detail below. In the detailed description below, many specific details are proposed to fully understand the present invention. However, it is obvious to those skilled in the art that the present invention can also be implemented without these specific details. The following description of the embodiments is only for a better understanding of the present invention by illustrating examples of the present invention. The present invention is not limited to any specific settings and methods provided below, but covers all product structures, any improvements, replacements, etc. of methods covered without departing from the spirit of the present invention.
[0059] The following is a SiC prepreg-infiltration process f The specific implementation of the present invention is further described by taking a laminate of pure 0° ply of SiC composite material as the test object, and carrying out the test of fiber matrix interface shear strength and matrix fracture energy. The example is only used to explain and illustrate the present invention and does not constitute any limitation to the present invention. In each of the drawings and the following description, well-known structures and technologies are not shown to avoid unnecessary ambiguity of the present invention.
[0060] Geometric description:
[0061] Prepreg-SiC prepared by melt infiltration process f The configuration and geometric dimensions of the standard tensile specimen of pure 0° ply of / SiC composite materials are as follows Figure 2 As shown. The fiber volume fraction V of the material f The matrix E was measured by nanoindentation test technology. m According to the information provided by the fiber manufacturer, the modulus of SiC fiber E f is 380 GPa, and the radius R of the SiC fiber is 6.5 μm.
[0062] The method of the present invention is used to prepare the above-mentioned pure 0° laminated SiC f The steps for testing the fiber-matrix interface shear strength and matrix fracture energy of SiC composites are as follows:
[0063] 1. According to the test piece size recommended by GJB 6475-2008, in SiC f A tensile test piece 1 was cut from a laminate of pure 0° ply of / SiC composite material. The test piece was a standard tensile specimen. The specific configuration and geometric dimensions are as follows: Figure 2 shown.
[0064] 2. Clamp the tensile test piece to the wedge-shaped clamp 2 and the wedge-shaped clamp 3 on the testing machine, install the extensometer 5 to the middle working section of the test piece. If it is a test at room temperature, install the acoustic emission probe 4 for room temperature test to the surface of the gauge section of the test piece. If it is a test at high temperature, place the working section of the test piece in a high-temperature furnace 8, pass the acoustic emission signal lead-out device 6 through the high-temperature furnace 8, and then stick the acoustic emission probe 7 for high-temperature test to the part of the acoustic emission signal lead-out device 6 outside the high-temperature furnace 8.
[0065] 3. Use displacement loading mode to perform tensile loading on the tensile test piece 1. At the same time, collect acoustic emission signals during the loading process, and record the stress-strain curve measured by the extensometer and the testing machine, such as Figure 3 As shown in the figure, the loading and data collection continued until the specimen 1 broke.
[0066] 4. Remove the broken test piece 1 to obtain the left half 9 and the right half 10 of the test piece after fracture. Cut a rectangular strip of 5 mm in length, 3 mm in width, and the same thickness as the test piece near the left fracture 11 of the test piece after fracture, in the middle of the width direction of the working section of the left half 9 of the test piece after fracture, as the mirror image sample 13 obtained near the left fracture. Alternatively, cut a rectangular strip of 5 mm in length, 3 mm in width, and the same thickness as the test piece near the left fracture 12 of the test piece after fracture, in the middle of the width direction of the working section of the left half 10 of the test piece after fracture, as the mirror image sample 14 obtained near the right fracture.
[0067] 5. Use diamond paste to polish one side of the mirror sample 13 obtained near the left fracture in the width direction to obtain a section surface 15 as the side to be observed. Figure 6 shown.
[0068] 6. Use a scanning electron microscope to observe the cross-section surface 15 of the mirror sample 13, use the image processing software provided by the electron microscope device to perform margin segmentation on the image, identify the matrix cracks according to the difference in grayscale values, and mark them on the image, such as Figure 7 The longitudinal irregular lines shown are indicative of cracks.
[0069] 7. Using the above-mentioned image with matrix cracks marked, count the matrix crack spacing and calculate the average value to obtain the matrix crack spacing Z when the sample is completely fractured. u , the value is about 220μm.
[0070] 8. Using the time, load, strain, and acoustic emission energy data collected during the tensile test loading process, with time as the link, the stress and normalized acoustic emission cumulative energy values are matched, and a curve is drawn with stress as the abscissa and normalized acoustic emission cumulative energy as the ordinate, such as Figure 8 shown.
[0071] 9. According to the tensile stress-strain curve of the test piece, identify the stress value σ when the matrix crack is saturated s The specific method is Figure 5 The stress value corresponding to the starting point of the last approximate linear segment (i.e., the third segment 18) marked on the curve is taken as σ s , the value is 450MPa. Figure 5 The material tensile stress-strain curve shown is divided into three sections, wherein the first section 16 is the initial linear section, the second section 17 is the intermediate nonlinear transition section, and the third section 18 is the final approximate linear section, wherein the starting moment of the final approximate linear section corresponds to the crack reaching a saturated state, and the corresponding stress level at this time is the stress value when the matrix crack is saturated.
[0072] 10. Take the difference between the curves with stress on the horizontal axis and normalized acoustic emission cumulative energy on the vertical axis to determine the stress as σ s The normalized acoustic emission cumulative energy E corresponding to s , the value is 0.82, such as Figure 8 shown.
[0073] 11. According to the law that the normalized acoustic emission cumulative energy is proportional to the matrix density (the number of cracks within 1 mm), and inversely proportional to the matrix crack spacing, the matrix crack spacing Z when the matrix crack is saturated is calculated according to formula (1): s .
[0074]
[0075] Among them, Z s is the matrix crack spacing when the matrix crack is saturated; Z u is the matrix crack spacing when the specimen is completely fractured; E s is the normalized acoustic emission cumulative energy corresponding to the saturation of the matrix crack.
[0076] 12. According to the stress value σ when the matrix crack is saturated, s , matrix crack spacing Z s , the fiber-matrix interface shear strength S is calculated using the theoretical formula (2). In addition, the matrix fracture energy Γ can also be calculated using formula (3): m .
[0077]
[0078] Where S is the fiber-matrix interface shear strength; R is the fiber radius; E m is the matrix modulus; E f is the fiber modulus; V f is the fiber volume fraction; σ s is the stress value when the matrix crack is saturated; Zs is the crack spacing when the matrix cracks are saturated.
[0079]
[0080] Among them, Γ m is the matrix fracture energy; E0 is the tensile modulus of the material, taken as the slope of the initial linear segment of the tensile stress-strain curve.
[0081] For this implementation case, we identify s =450MPa, reverse calculation yields Z s =180μm, and the necessary parameters, namely V f =25%, E m =360GPa, E f =380GPa, E0=300GPa, R=6.5μm. Substituting the above into formula (2) and formula (3), the values of fiber matrix interface shear strength and matrix fracture energy are calculated to be 46.2MPa and 24.6J / m 2 .
[0082] In summary, the present invention proposes a method for determining SiC based on the acoustic emission signal, stress-strain curve, and fracture observation of the sample after continuous tensile loading of the standard spline. f A test method for the fiber-matrix interface shear strength and matrix fracture energy of SiC / SiC composite laminate materials. To overcome the shortcoming of the existing interface strength micromechanics test method that requires separate sample preparation, it is only necessary to use the conventional standard spline tensile test to add acoustic emission signal collection and analysis and post-test fracture analysis, which greatly simplifies the test and can more realistically characterize the fiber-matrix interface shear strength and matrix fracture strength of the block laminate material. The stress value at the saturation of the matrix crack is obtained based on the stress-strain curve identification, which can greatly improve the identification accuracy of the stress value at the saturation of the matrix crack. At the same time, it is also possible to test SiC at high temperature without the need for special testing equipment. f / SiC composite material fiber matrix interface shear strength and matrix fracture strength. Can achieve the following technical effects:
[0083] (1) Based on the rule that the cumulative energy is linearly proportional to the crack density, the crack spacing under the saturation stress of the matrix crack is indirectly calculated by the normalized acoustic emission cumulative energy, thereby measuring the interface shear strength and matrix fracture strength.
[0084] (2) There is no need to specially prepare samples for micromechanical testing, or to use precise micromechanical testing equipment. The fiber-matrix interface shear strength and matrix fracture energy can be measured using only the data information obtained before and after the macroscopic test, which greatly reduces the testing cost.
[0085] (3) Solved the problem that existing methods cannot test SiC f / SiC composites at high temperatures and the problem of interface shear strength and matrix fracture energy.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the field can easily think of various equivalent modifications or substitutions within the technical scope disclosed by the present invention, and these modifications or substitutions should all be covered within the protection scope of the present invention.
Claims
1. A test SiC f The method for measuring the shear strength of the fiber matrix interface of a SiC / SiC ceramic matrix composite material is characterized in that: Here are the steps: Step 1: On SiC f / SiC composite material pure 0° laminated cutting tensile test pieces; Step 2: Clamp the tensile test piece onto the clamping block of the testing machine, install the extensometer onto the middle working section of the test piece, and install the acoustic emission probe onto the surface of the gauge section of the test piece or onto the acoustic emission signal extraction device; Step 3: Use displacement loading mode to perform tensile loading on the test piece, collect acoustic emission signals during the loading process, and record the stress-strain curve measured by the extensometer and the testing machine, and continue loading and collecting data until the test piece breaks; Step 4: Remove the broken test piece, and cut a rectangular strip of the same thickness as the test piece from the middle of the width direction near the fracture of the working section of the test piece after the fracture, as a mirror sample; Step 5: polishing one side of the mirror image sample in the width direction with diamond paste; Step 6: Observe the polished side of the mirror sample, perform margin segmentation on the image, identify matrix cracks according to the difference in grayscale values, and mark them on the image; Step 7: Using the image, count the matrix crack spacing and calculate the average value to obtain the matrix crack spacing Z when the sample is completely broken. u ; Step 8: Using the time, load, strain, and acoustic emission energy data collected during the tensile test loading process, with time as the link, the stress and the normalized acoustic emission cumulative energy values are matched to draw a curve with the stress as the abscissa and the normalized acoustic emission cumulative energy as the ordinate; Step 9: According to the tensile stress-strain curve of the test piece, identify the stress value σ when the matrix crack is saturated s ; Step 10: The stress is σ obtained by subtracting the stress-normalized acoustic emission cumulative energy curve. s The normalized acoustic emission cumulative energy E corresponding to s ; Step 11: According to the law that the normalized acoustic emission cumulative energy is linearly proportional to the matrix density and thus linearly inversely proportional to the matrix crack spacing, the matrix crack spacing Z when the matrix crack is saturated is calculated according to formula (1): s ; Among them, Z s is the matrix crack spacing when the matrix crack is saturated; Z u is the matrix crack spacing when the specimen is completely fractured; E s is the normalized acoustic emission cumulative energy corresponding to the saturation of matrix cracks; Step 12: Based on the stress value σ when the matrix crack is saturated, s , matrix crack spacing Z s , the fiber-matrix interface shear strength S is calculated using the theoretical formula (2), and the matrix fracture energy Γ is calculated using the formula (3) m ; Where S is the fiber-matrix interface shear strength; R is the fiber radius; E m is the matrix modulus; E f is the fiber modulus; V f is the fiber volume fraction; σ s is the stress value when the matrix crack is saturated; Z s is the crack spacing when the matrix cracks are saturated. Among them, Γ m is the matrix fracture energy; E0 is the tensile modulus of the material, taken as the slope of the linear segment of the tensile stress-strain curve.
2. The method according to claim 1, characterized in that The method is applicable to a ceramic matrix composite material with a continuous SiC fiber reinforced SiC matrix in a layering process.
3. The method according to claim 1, characterized in that The dimensions of the tensile test piece in step 1 are prepared according to GJB6475-2008.
4. The method according to claim 1, characterized in that: In step 4, the length of the rectangular strip is 3-5 times the thickness of the sample, and the width is 1-2 times the thickness of the sample.
5. The method according to claim 1, characterized in that SiC used in step 1 f Pure 0° laminates of SiC composite materials can also be replaced with 0° / 90° alternating laminates.
6. The method according to claim 1, characterized in that The method is applicable to testing at room temperature and high temperature, wherein the high temperature is 600-1400 degrees Celsius.
7. The method according to claim 1, characterized in that Steps 6 and 7 use means to identify matrix cracks and measure the matrix crack spacing Z u .
8. The method according to claim 1, characterized in that In step 9, the stress value σ when the matrix crack is saturated is identified according to the tensile stress-strain curve. s The method is to mark the starting point of the last linear segment σ on the curve. s The corresponding stress value, as σ s .
9. The method according to claim 1, characterized in that: In step 12, the fiber-matrix interface shear strength S and matrix fracture energy Γ are calculated. m The fiber modulus E involved in the theoretical formula f , matrix modulus E m Obtained using nanoindentation testing technology or traditional macroscopic mechanical testing methods.
10. The method according to claim 2, characterized in that The method is suitable for SiC prepared by prepreg-melt infiltration process f / SiC composite laminates.
Citation Information
Cited By
Composite material laminated sheet interlayer damage identification and failure determination method, device, equipment and medium
CN121347679A